2007
DOI: 10.1161/circulationaha.106.664979
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Hospital Mortality and Use of Percutaneous Coronary Intervention in Acute Myocardial Infarction

Abstract: Background-Women with acute myocardial infarction have a higher hospital mortality rate than men. This difference has been ascribed to their older age, more frequent comorbidities, and less frequent use of revascularization. The aim of this study is to assess these factors in relation to excess mortality in women. Methods and Results-All hospital admissions in France with a discharge diagnosis of acute myocardial infarction were extracted from the national payment database. Logistic regression on mortality was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
3
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(158 citation statements)
references
References 37 publications
12
130
3
13
Order By: Relevance
“…Females are more likely to die than males. This is consistent with care being more protective for males than for females possibly because of biological differences like the smaller target vessel size and the more important vessel tortuosity of females (Milcent et al, 2007). Also, the propensity to die increases with age.…”
Section: Econometric Methodssupporting
confidence: 79%
“…Females are more likely to die than males. This is consistent with care being more protective for males than for females possibly because of biological differences like the smaller target vessel size and the more important vessel tortuosity of females (Milcent et al, 2007). Also, the propensity to die increases with age.…”
Section: Econometric Methodssupporting
confidence: 79%
“…Furthermore, our study shows that the older the patient was, the higher the odds of dying in the hospital. These results are in concordance with several other studies, which conclude that females with myocardial infarction have higher in-hospital mortality compared to men [5][6][7][8][9][10]. Also similar to other studies, women in this sample were older and smoked less than men [10].…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have indicated that shortand long-term post-MI (Koek et al 2006;Milcent et al 2007) and post-stroke mortality is higher in women than in men (Appelros et al 2009;Lewsey et al 2009;Appelros et al 2010;Andersen et al 2011). Some studies found that the female disadvantage in post-stroke survival was limited to younger ages (Vaccarino et al 1998(Vaccarino et al , 1999(Vaccarino et al , 2001Nielsen et al 2014), while others found that rates of post-MI and post-stroke survival did not differ significantly by gender after the baseline and clinical characteristics were taken into account (Galatius et al 1996;Herman et al 1997;MacIntyre et al 2001;Di Carlo et al 2003;Isaksson et al 2011;Olsen et al 2012).…”
Section: Sex Differences In Morbiditymentioning
confidence: 99%